KETERAMPILAN KOLABORASI PESERTA DIDIK MATERI GOTONG ROYONG LINGKUNGAN MASYARAKAT KELAS IV SDN 1 TRENCENG TULUNGAGUNG - Intan Faiza Dilla; Nourma Oktaviarini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Collaboration skills are a must-have to be able to work together effectively. These collaboration skills are important to develop early on to prepare for the world of work and education. The purpose of this study is to describe and analyze the collaboration skills of gotong royong material in the community environment of class IV SDN 1 Trenceng Tulungagung. Using descriptive qualitative with data collection through observation, interviews and documentation. The results showed that the average indicator of actively contributing was 2.9 with a percentage of 73%, working productively was 2.9 with a percentage of 73%, being flexible and compromising 3.2 with a percentage of 81.9%, managing projects well 3 with a percentage of 76.3%, respecting fellow members 2.8 with a percentage of 72%, and being responsible 3.2 with a percentage of 81.9%. It is concluded that the collaboration skills of students on the material of mutual cooperation in the community environment of class IV SDN 1 Trenceng are included in the high predicate.